Step
*
1
of Lemma
qsum_product
1. a : ℤ
2. b : ℤ
3. c : ℤ
4. d : ℤ
5. x : {a..b + 1-} ⟶ ℚ
6. y : {c..d + 1-} ⟶ ℚ
⊢ (Σc ≤ j < d. y[j] * Σa ≤ i < b. x[i]) = Σa ≤ i < b. Σc ≤ j < d. x[i] * y[j] ∈ ℚ
BY
{ ((RWO "qsum-linearity1<" 0 THEN Auto)⋅ THEN EqCD THEN Auto) }
Latex:
Latex:
1. a : \mBbbZ{}
2. b : \mBbbZ{}
3. c : \mBbbZ{}
4. d : \mBbbZ{}
5. x : \{a..b + 1\msupminus{}\} {}\mrightarrow{} \mBbbQ{}
6. y : \{c..d + 1\msupminus{}\} {}\mrightarrow{} \mBbbQ{}
\mvdash{} (\mSigma{}c \mleq{} j < d. y[j] * \mSigma{}a \mleq{} i < b. x[i]) = \mSigma{}a \mleq{} i < b. \mSigma{}c \mleq{} j < d. x[i] * y[j]
By
Latex:
((RWO "qsum-linearity1<" 0 THEN Auto)\mcdot{} THEN EqCD THEN Auto)
Home
Index